2014
DOI: 10.1002/cem.2634
|View full text |Cite
|
Sign up to set email alerts
|

Decompositions using maximum signal factors

Abstract: Maximum autocorrelation factors (MAF) and whitened principal components analysis are gaining popularity as tools for exploratory analysis of hyperspectral images. This paper shows that the two approaches are mathematically identical when signal and noise (clutter) are defined similarly. It also shows that the MAF metaphor can be generalized to encompass a wide variety of signal processing objectives referred to generically as maximum signal factors while retaining the interpretability of principal components a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…It has been shown that combining target and anomaly detection approaches (e.g., PCA can be considered an anomaly detection approach) allows for empirically enabling target detection to be more sensitive and more relevant to image specific scenarios. 62 Thus, "targeted anomaly detection" synergistically employs laboratory measured spectra with empirical detection methods to provide an approach optimized for individual scenarios and will be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that combining target and anomaly detection approaches (e.g., PCA can be considered an anomaly detection approach) allows for empirically enabling target detection to be more sensitive and more relevant to image specific scenarios. 62 Thus, "targeted anomaly detection" synergistically employs laboratory measured spectra with empirical detection methods to provide an approach optimized for individual scenarios and will be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a surge interest in the theoretical properties and practicality of MAF (Gallagher et al, 2014). In fisheries, Erzini (2005) investigated fishery catches using multiple time series of environmental parameters and compared MAF with dynamic factor analysis.…”
Section: Functional Principal Component Analysis (Fpca)mentioning
confidence: 99%
“…Some applications of MAF to multiple time series analysis are given in Switzer and Green [1984], Shapiro and Switzer [1989], Gallagher et al [2014]. Our interest in MAF derives from applications to the analysis of multiple time series of climate proxy data from tree ring measurements, described in Section 6.…”
Section: Maf -Maximum Autocorrelation Factorsmentioning
confidence: 99%